MEASUREMENT OF INLIS APPLICATION QUALITY USING MCCALL METHOD - Silfia Andini; Hari Marfalino; Rima Liana Gema (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
The Inlis application at the Archives and Library Office of West Sumatra Province is used to manage the lending and book return process carried out by each library member. With the library system, it can help the librarians to know the flow of books in and out of the delay in returning the library members to determine the fines to be paid by the members. Based on this the authors will measure the quality of the Library Information System because in this system the quality of the system is unknown, thus identifying the accuracy, completeness and quality of the software in the Inlis Application. The measurement method in this study is the McCall Method. The results based on the McCall Method show that the quality of the Inlis Application is good with a percentage value of 73%, with the best indicator value, namely reliability with a yield of 73% and the worst indicator value, ie with a result of 51%